Functionalist and usage-based approaches to the study of language : in honor of Joan L. Bybee - Smith, K. Aaron (Kelly Aaron), 1965-; Nordquist, Dawn; Bybee, Joan L. (Studies in language companion series, 2018)
The contributions to this volume honor Joan Bybee's 2005 LSA Presidential address "Grammar is Usage and Usage is Grammar," as a cumulative articulation of Professor Bybee's long and influential career in linguistics. The volume begins with a functional examination of child language acquisition of ergative languages. The next three contributions successively investigate the grammaticalization of Greek postural verbs, Spanish third person pronouns, and American Sign Language topicalization constructions. The two following papers report on usage-based phonological studies of Spanish /s/ and /d/, respectively. The book concludes with four papers that address usage-based effects concerning the grammatical status of ain't in African American English, Spanish verbs of "becoming", and English lexis and prefabs.